Ultrasound-detected synovial abnormalities are frequent in clinically inactive juvenile idiopathic arthritis, but do not predict a flare of synovitis. Issue 2 (26th June 2012) - Magni-Manzoni, Silvia; Scirè, Carlo Alberto; Ravelli, Angelo; Klersy, Catherine; Rossi, Silvia; Muratore, Valentina; Visconti, Chiara; Lanni, Stefano; Merli, Pietro; Montecucco, Carlomaurizio
Abstract : Objectives: To investigate whether children with juvenile idiopathic arthritis (JIA) in clinical remission have subclinical synovial disease on ultrasound, and whether ultrasound abnormalities predict an early flare of synovitis. Methods: Thirty-nine consecutive children who had clinically defined inactive disease (ID) for a minimum of 3 months underwent ultrasound assessment of 52 joints. All joints were scanned for synovial hyperplasia, joint effusion, power Doppler (PD) signal and tenosynovitis. Patients were then followed clinically for up to 2 years until a flare of synovitis occurred in one or more joints, or until the 2-year visit if the disease remained in clinical remission. Results: Synovial hyperplasia, joint effusion, PD signal and tenosynovitis in at least one joint were detected in 76.9%, 66.7%, 33.3% and 15.4% of patients, respectively. During the 2-year follow-up, 24 patients (61.5%) experienced sustained ID, whereas 15 patients (38.5%) had a flare of synovitis in a total of 45 joints after a median of 10.6 months (range 6.3–13.7 months). At study entry, the rate of synovial hyperplasia, joint effusion and tenosynovitis was comparable between patients with persistent ID and patients with synovitis flare, whereas patients with persistent ID had a greater frequency of PD signal than patients with synovitis flare. Only 17 of the 45 flared joints had ultrasound abnormalities at study entry. Conclusion: The authors found that ultrasound-detected synovial abnormalities are common in children with JIA in clinical remission. However, the presence of ultrasound pathology did not predict an early flare of synovitis in the affected joints.